CORRESPONDENCE BETWEEN MODELS AND FACTORS OF STUDENT ERRORS IN SOLVING CONTEXTUAL PROBLEMS - Fiki Alghadari; Audi Yundayani; Abdul Halim Abdullah (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2022)
The acquisition of knowledge assists students in navigating life, but their skill configuration is unstable when confronted with contextual problems. The fact that they make problem-solving errors is a stability problem that stems from existential situations. This study examined students' errors in solving contextual math word problems. The respondents were 36 Jakarta junior high school students. This work employs an existential design informed by phenomenology to lessen the connection between the model and error-causing. Newman's strategy found various types of errors. The researchers then investigated the error model and the root causes of the detected errors through interviews. According to the ontological investigation, seven correspondences were discovered between the error models and the causative factors, namely comprehension, transformation, and process skills, so that the origin of occurrences remained unchanged. Deficiencies in process skills cause the majority of correspondence. The phenomenological reduction of the correspondence demonstrates that students are not always engaged in higher-order thinking and tend to concentrate on the procedural knowledge learning process. It can be concluded that the learning process must encourage students' higher-order thinking. When students learn and gain experience through misunderstandings and transformations, they will demonstrate constructive efforts and computational thinking by troubleshooting the problem-solving strategy. Pengetahuan memfasilitasi siswa dalam menghadapi kehidupan, tetapi konfigurasi kemampuan mereka belum mantap ketika dihadapkan pada tantangan kontekstual. Siswa membuat kesalahan dalam penyelesaian adalah masalah stabilitas yang bersumber dari kondisi eksistensial. Penelitian ini bertujuan untuk mengevaluasi kesalahan siswa dalam penyelesaian soal cerita matematika pada setting kontekstual. Responden adalah 36 siswa MTs di Jakarta. Penelitian ini menggunakan desain eksistensial pada perspektif fenomenologis untuk mereduksi korespondensi antara model dan faktor penyebab kesalahan. Jenis kesalahan diidentifikasi dengan pendekatan Newman, kemudian peneliti mengeksplorasi model kesalahan dan faktor penyebab dari jenis-jenis kesalahan yang teridentifikasi melalui wawancara. Hasil penelitian menemukan tujuh korespondensi antara model kesalahan dengan faktor penyebabnya adalah pemahaman, transformasi, dan keterampilan proses, sehingga sumber kejadian menurut kajian ontologis juga tetap konstan. Mayoritas korespondensi dihasilkan dari kesalahan keterampilan proses. Reduksi fenomenologis dari korespondensi tersebut mengungkapkan bahwa siswa tidak selalu terlibat dalam pemikiran tingkat tinggi dan cenderung menitikberatkan proses pembelajaran pada pengetahuan prosedural. Dapat disimpulkan bahwa proses pembelajaran harus mendorong berpikir tingkat tinggi siswa. Ketika siswa belajar dan memperoleh pengalaman melalui kesalahpahaman dan transformasi, mereka akan mendemonstrasikan upaya konstruktif dan pemikiran komputasi dengan pemecahan masalah strategi pemecahan masalah.